Celebration of Another Nation?: Australia's Bicentenary in Britain - Crawford, Robert G. (History compass, 2008)
Historians and contemporary critics have generally taken a dim view of Australia's Bicentennial celebrations in 1988, labelling them a wasted opportunity to redress the nation's previous wrongs. While these claims certainly have a point, they have nevertheless tended to adopt a simplified image of the Bicentenary and its significance. This article re-visits the Bicentenary by undertaking a more nuanced reading of the events and discourse surrounding the celebrations and commemorations by different groups in the United Kingdom during 1987 and 1988. These Bicentennial events were more than mere celebrations; they were an opportunity for both Britons and Australians to reflect on their history, their place in the world, and their sense of identity. By examining the different meanings associated with the Bicentenary, this article will suggest that the Bicentennial events provided an important opportunity for reflection that also revealed the state of Australian nationhood in the post-imperial age.